Whole transcriptome sequencing identifies increased CXCR2 expression in PNH granulocytes. (1st February 2017) - Hosokawa, Kohei; Kajigaya, Sachiko; Keyvanfar, Keyvan; Qiao, Wangmin; Xie, Yanling; Biancotto, Angelique; Townsley, Danielle M.; Feng, Xingmin; Young, Neal S.
Summary: The aetiology of paroxysmal nocturnal haemoglobinuria (PNH) is a somatic mutation in the X‐linked phosphatidylinositol glycan class A gene ( PIGA ), resulting in global deficiency of glycosyl phosphatidylinositol–anchored proteins (GPI‐APs). This study applied RNA‐sequencing to examine functional effects of the PIGA mutation in human granulocytes. CXCR2 expression was increased in GPI‐AP ‐ compared to GPI‐AP + granulocytes. Macrophage migration inhibitory factor, a CXCR2 agonist, was significantly higher in plasma of PNH patients. Nuclear factor‐κB phosphorylation was upregulated in GPI‐AP − compared with GPI‐AP + granulocytes. Our data suggest novel mechanisms in PNH, not obviously predicted by decreased production of the GPI moiety.